МОТИВАЦІЯ НАВЧАЛЬНО-ДОСЛІДНИЦЬКОЇ РОБОТИ В ОСОБИСТІСНО-ОРІЄНТОВАНОМУ НАВЧАННІ (Педагогіка вищої та середньої школи, 2004)
The article shows the role o f motivation as a basic factor of student's readiness to teaching and research activity, singles out groups of motives of scientific-reseat work, outlines some ways of step-by-step purposeful development o f motives of teaching-research work, with the object of raising of effectiveness of readiness to this type of activity under conditions of personal oriented training.